Analyzing the Formula for the Mother Tongue’s Interference in Daily Arabic Conversation/تحليل صيغة تدخل اللغة الأم في المحادثة اليومية باللغة العربية - Maimunah Maimunah; Haniah Mukhtar (UIN ANTASARI, 2021)
This research is focused on The interference mother language in arabic language use in the daily conversations of language. Nowadays, the very rapid advances in communication technology and science encourage humans to not only master one language, namely the Mother tongue, but also several foreign languages used in international forums, such as English and Arabic. Darul Hijrah Islamic Boarding School for girl in Martapura is one of the Islamic Boarding that requires students to use 2 languages in daily conversation, namely Arabic and English and apply a language environment to their acquisition. However, some students speak Arabic using elements of Indonesian language, grammar and mix with the Mother tongue during Arabic conversations. This is a qualitative research with a descriptive method. The subject of the research was the students' Arabic utterance. To analyze the data, the researcher used the following steps: data reduction, data presentation and conclusions, while the language speech data were analyzed using the error analysis method and comparative analysis